2000
DOI: 10.1093/alcalc/35.6.569
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Neutral Sphingomyelinase Participates in Ethanol-Induced Apoptosis in Hep G2 Cells

Abstract: The mechanism underlying ethanol-induced apoptosis in liver cells is not clear. Sphingomyelin (SM) metabolism is a novel signal transduction pathway that has an impact on apoptosis in many cell types. We investigated whether the SM pathway is involved in ethanol-induced apoptosis in the liver. Hep G2 cells were treated with ethanol followed by assaying apoptosis, sphingomyelinase (SMase) activity, caspase-3 activity, and the changes of SM content in the cells. We found that ethanol dose-dependently increased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 28 publications
3
22
1
Order By: Relevance
“…These increases were associated with increased activity of acidic sphingomyelinase (Smpd1), which uses sphingomyelin as a substrate for ceramide synthesis. There was, however, no corresponding decrease in sphingomyelin reported ( 6,9,56 ). In our studies, we found no change in the mRNA level of Smpd1 in alcohol-fed mice.…”
Section: Hepatic Sphingolipid Levels Are Increased Following Alcohol contrasting
confidence: 72%
“…These increases were associated with increased activity of acidic sphingomyelinase (Smpd1), which uses sphingomyelin as a substrate for ceramide synthesis. There was, however, no corresponding decrease in sphingomyelin reported ( 6,9,56 ). In our studies, we found no change in the mRNA level of Smpd1 in alcohol-fed mice.…”
Section: Hepatic Sphingolipid Levels Are Increased Following Alcohol contrasting
confidence: 72%
“…Caspase activities were assayed using their specific substrates as described (17). Briefly, 3ϫ10 6 cells were incubated with RPMI-1640 medium containing boswellic acids or camptothecin for 24 h. The cells were lyzed in 80 µl of ice-cold lysis buffer containing 50 mM HEPES, 100 mM NaCl, 0.1% CHAPS, 1 mM DTT and 0.1 mM EDTA, pH 7.4 and put on ice for 5 min, followed by centrifugation at 10 000 g for 15 min at 4°C.…”
Section: Assay Activities Of Caspase-3 Caspase-8 and Caspase-9mentioning
confidence: 99%
“…A dose-dependent activation of neutral sphingomyelinase and a decrease in sphingomyelin content was observed in liver cells [9]. Ethanol treatment of astrocytes was associated with the stimulation of neutral and acid sphingomyelinase, ceramide generation and the subsequent activation of signaling pathways implicated in cell death [10].…”
Section: Introductionmentioning
confidence: 99%